THE APPLICATION OF ENTREPRENEURIAL MOTIVATION AND SOCIAL MEDIA USE ON ENTREPRENEURIAL INTEREST AMONG GENERATION Z IN WEST JAKARTA - Haliza, Sharyn; Widjaja, Oey Hannes (Graduate Program of Universitas Tarumanagara, 2025)
This research aims to examine the influence of entrepreneurial motivation and social media usage on entrepreneurial interest among Generation Z students at Tarumanagara University. The population of this research consists of Generation Z students enrolled at Tarumanagara University. A total of 100 students were selected as the sample using purposive sampling. Data were collected through a questionnaire distributed online via Google Forms. The data analysis technique employed the SmartPLS version 4 method. The results of the study indicate that entrepreneurial motivation and social media have a positive and significant effect on entrepreneurial interest among Generation Z students at Tarumanagara University.